Study of binding substances for briquetting of small classes of coals KR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The physicochemical, technological properties, and elemental composition of coal from several deposits in the Kyrgyz Republic were studied. It was established that coal from the Kara-Keche and Ak-Ulak deposits will not briquette without the use of binders . Due to their low bitumen content (0.44% to 1.45%) and low yields of primary resin, coal from the Kara-Keche and Ak-Ulak deposits will not briquette without the use of binders. Binders made from locally available, affordable raw materials were discovered, allowing for the production of durable briquettes. Optimal briquetting process parameters were established.
Keywords: coal fines, binders, briquetting, briquettes, optimal parameters, resin, bitumen